Human skin‐depigmenting effects of resveratryl triglycolate, a hybrid compound of resveratrol and glycolic acid. (7th June 2018) - Jo, D. J.; Seok, J. K.; Kim, S. Y.; Park, W.; Baek, J. H.; Kim, Y. M.; Boo, Y. C.
Abstract: Objectives: Resveratryl triglycolate (RTG) is a hybrid compound derived by the esterification of resveratrol with glycolic acid. This compound has been previously shown to inhibit cellular melanin synthesis in vitro . This study aimed to examine the in vivo skin‐depigmenting efficacy of RTG in human participants. Methods: In total, 22 women aged between 25 and 49 years with Fitzpatrick skin type III or IV were enrolled. Their forearms were exposed to UV to induce artificial pigmentation. The test product containing 0.4% RTG or the control product was applied twice daily for up to 8 weeks after the artificial pigmentation. The participants visited the research centre every 2 weeks and were subjected to skin assessments. Results: Visual assessment of pigmentation degree and instrumental analysis of melanin index, skin lightness (L* value) and skin colour (individual typology angle, ITA o ) indicated enhanced depigmentation of the skin in the test group, compared with the control group, in Weeks 6 and 8 ( P < 0.05). No adverse skin reactions were observed in any of the participants during the entire test. Conclusion: This study demonstrated the skin‐depigmenting effects of RTG in human participants. Abstract : Resveratryl triglycolate (RTG) is a hybrid compound derived by the esterification of resveratrol with glycolic acid. In this study, the test product containing 0.4% RTG showed the skin‐depigmenting effects in human participants.